Fruits basket. Volume 4 - Takaya, Natsuki (Los Angeles, Calif. : Tokyopop, 2004)
An orphaned high school freshman who lives with a family possessed by the spirits of the Chinese zodiac is grateful for their generosity, but the longer she lives with them, the more they realize what a blessing she is, as well.
"This book is printed "manga-style" in the authentic Japanese right-to-left format"--Colophon.
"First published in Japan in 2000 by Hakusensha, Inc., Tokyo"--P. facing t.p.
Contributing writer, Adam Arnold.
Teen age 13+.
Translated from the Japanese.
Keywords: Comic books, strips, etc. -- Japan; Graphic novels